Serious suicidal behaviors: Socio-demographic and clinical features in a multinational, multicenter sample. (January 2014) - Carli, Vladimir; Mandelli, Laura; Zaninotto, Leonardo; Iosue, Miriam; Hadlaczky, Gergo; Wasserman, Danuta; Hegerl, Ulrich; Värnik, Airi; Reisch, Thomas; Pfuhlmann, Bruno; Maloney, Julia; Schmidtke, Armin; et al.
Abstract Background: Declared suicidal intent and physical danger are both considered important components in defining suicidal behaviors (SB). Aims: 1) To investigate characteristics of serious suicidal behaviors (SSB), defined by either suicidal intent or lethality; 2) To determine any difference in terms of socio-demographic, clinical and/or service usage variables between SSB and non-serious suicidal behaviors (NSSB). Methods: A total of 2631 contacts for SB were registered in the context of the MONSUE (Monitoring Suicidal Behavior in Europe) study project. Demographic and clinical information were registered. ICD-10 was used for classifying data about psychiatric diagnoses, methods used for SB and injuries reported. Clear intentionality, high-case fatality methods and serious injuries all defined SSB (n = 1169; 44.4%) Results: SSB were more often preceded by a contact with an inpatient (either psychiatric or somatic) rather than an outpatient service. Among those having a previous history of SB, SSB subjects had fewer contacts with health services before the previous attempt. The strongest predictors for SSB appeared to be older age and not professing a religion. Conclusion: Many of the known factors contributing to the risk of completed suicide were also present for SSB. Our findings on service usage by suicide attempters show which aspects of mental health services should be strengthened in order to improve suicide prevention.